Bedload Transport in Gravel Streams - Surface Versus Subsurface Based Transport Analysis - Hafez Shaheen; Panayiotis Diplas (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
Fluid forces and the quantity and ranges of grain sizes present on a streambed are the important factors affecting the transport of sediments. Most bedload transport models are based on single grain size parameter that represents either the surface or the subsurface bed material. Fractional bedload transport analysis is used to account for the different grain sizes. Surface versus subsurface-based fractional analysis of available bedload transport data are compared and the effect of the selection of the dimensionless reference bedload transport parameter is investigated. Fractional analysis has indicated that it is referenced to the size distribution of the bed surface rather than the subsurface and that its necessity increases for bedload data sets that fall closer to the lower end near threshold conditions. The reference value for the dimensionless bedload parameter used in this paper falls within the lower range of the analyzed bedload data set.